Identification of Eight Point Mutations in Protein S Deficiency Type I – Analysis of 15 Pedigrees - Reitsma, P H; Gómez, E; Poort, S R; Bertina, R M (Thrombosis and Haemostasis, 1995)
We describe molecular genetic studies of 15 patients with protein S deficiency type I (i. e. reduced total protein S antigen). All the exons of the PROS 1 gene were analyzed both by PCR and direct sequencing in all 15 probands. This analysis led to the identification of point mutations affecting eight individuals. One of these mutations (codon -25, insertion of T) has been described previously in a Dutch pedigree. The other mutations are novel and all are located in exons that code for the protein S domain that is homologous to the steroid hormone binding globulins. They include two amino acid replacements (one individual with 340 Gly → Val, and two individuals with 467 → Val Gly), and four frameshift mutations due to either one bp deletions (in codon 261 deletion of T and in codon 267 deletion of G) or insertions (in codon 565 insertion T and after codon 578 insertion of C). Studies performed in six families (totalling 43 subjects) showed cosegregation of the genetic abnormality with reduced plasma protein S levels, and provided genetic evidence for a heterozygous protein S deficiency in 25 of them. The yield of mutations in this study (53%) confirms that the percentage of protein S deficient cases in which a point mutation is found remains low.